Revitalisasi Pusat Kebudayaan dan Pertunjukan Seni Tradisional di Kabupaten Purworejo dengan Pendekatan Desain Infill - Caesar Corima Krisna Suci; Desy Ayu Krisna Murti (JURNAL ARSITEKTUR PENDAPA, 2023)
The need to revive ancestral traditions in Purworejo district which many people in Purworejo have not known for a long time. The existence of a government work program to welcome the existence of the Tosan Aji Museum by building an Art Center is considered not to accommodate all traditional culture in Purworejo. The absence of a forum for intangible culture in Purworejo district is a major problem. The second problem is that dance studios do not have private practice areas, so only the home of the founder or the head of the studio serves as a place to place equipment, clothes and offices. Usually the dancers of each studio take turns to practice once a week at the district pavilion. Another reason is that the Dolalak dance, which is used as tourism branding for Purworejo Regency, has received a little less attention regarding its facilities. By studying the function and outer spatial circulation of the Cultural and Performance Center building in general, the condition of the Purworejo district and its traditional culture along with the architectural background of the existing building which is a cultural heritage building from colonial heritage. So using the Infill design approach will answer the problem from a design perspective. The facilities needed to answer the above problems are by designing the supporting mass layout of the performance space, namely the backstage building, dance studio, studio management office, and other public facilities such as control rooms, lobbies, merchandise, and convenience stores.